Doctoral success as ongoing quality business: A possible conceptual framework - Bitzer, EM (South African Journal of Higher Education, 2011)
The challenges involving doctoral non-completion and a lack of academic or scholarly quality are not restricted to putting the blame on doctoral candidates themselves, their supervisors or the institutions where they enrol. As candidates carry huge responsibilities when entering doctoral studies, success can be associated with an array of factors or challenges. Based on relevant literature, this article explores several such challenges related to potentially limiting or promoting doctoral success and quality. It proposes a preliminary theoretical or conceptual framework that might be useful for further investigating the phenomenon of doctoral study success associated with quality. It is suggested that doctoral success in higher education institutions represents a productive inter-relationship among a number of critical factors and in particular between academic mentoring and supervision on the one hand and institutional research and monitoring on the other.